UPAYA INDONESIA DALAM PERLINDUNGAN TENAGA KERJA INDONESIA DI VIETNAM PADA MASA PRESIDEN SUSILO BAMBANG YUDHOYONO (2009-2014) - M.Arif Rahman; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Many plight of migrant workers abroad, such as assault, rape, suicide, until not given wages for work. Many who view this problem due to the low level of education of migrant workers. But in addition to this, the lack of an integrated protection system of the country, both sending and destination countries, also contributed to the above facts. System protection for workers has yet to recognize the foreign workforce who work in the informal sector, both nationally and internationally. Law enforcement approach to the regulation of migration in destination countries tend to put undocumented migrant workers at a disadvantage, because they generally have to bear the consequences are less subjected to inhuman treatment and is often referred to as illegal. Issues that will be addressed in this study is "How legal protection for migrant workers in the State? '. The purpose of the discussion of this question will be discussed in the author for this study because the authors wanted to know what issues are arising in connection with the fate of migrant workers abroad, so that workers in the State looks neglected rights. Writing is normative legal research methods, because the authors did not conduct field studies. Materials studies the authors used only a secondary data only, which consists of primary legal materials in the form of legislation, secondary legal materials, in the form of books, papers, journals relating to the writing of this study. Keywords: protection, law, imigrant workers